2017
DOI: 10.1111/jocn.13849
|View full text |Cite
|
Sign up to set email alerts
|

Understanding management and support for domestic violence and abuse within emergency departments: A systematic literature review from 2000–2015

Abstract: Domestic violence and abuse has been shown to have a direct impact on the health and well-being of survivors who will often access emergency department services with direct injuries and associated medical conditions. This article is relevant to those working in the emergency department in raising awareness in a number of areas of practice for example the prevalence of male intimate partner violence survivors. Furthermore, patients do not always disclose domestic violence and abuse even in cases where there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 40 publications
(155 reference statements)
0
31
0
2
Order By: Relevance
“…Previous research showed that IPV screening was important for women who visit the ER [70]. While there is a debate about universal screening for IPV and universal screening for safety and providing universal information and education on IPV [71,72], it is agreed conducting any form of screening can help women disclose abuse, and help healthcare providers to properly respond to, and treat not only the physical and/or sexual, but also the psychological aspects of IPV [26,73,74]. Among Jewish women, no association was found between IPV screening and receiving information.…”
Section: The Effect Of Ipv Screening and Information Received On Suppmentioning
confidence: 99%
“…Previous research showed that IPV screening was important for women who visit the ER [70]. While there is a debate about universal screening for IPV and universal screening for safety and providing universal information and education on IPV [71,72], it is agreed conducting any form of screening can help women disclose abuse, and help healthcare providers to properly respond to, and treat not only the physical and/or sexual, but also the psychological aspects of IPV [26,73,74]. Among Jewish women, no association was found between IPV screening and receiving information.…”
Section: The Effect Of Ipv Screening and Information Received On Suppmentioning
confidence: 99%
“…Emergency departments treat a large number of women, with it being estimated that between 6% and 54% experience IPV and/or will probably experience it by their current or former partners, especially physical abuse and sexual coercion and particularly if they have little social support [ 15 , 29 , 31 , 52 , 53 ]. It has even been reported that many women who are murdered by their partners/former partners had resorted to emergency services [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…That is why they constitute a privileged attention unit, not only to treat any possible injuries, but also to actually help victims minimise their exposure to abuse, or even to get out of such situation [15,35]. However, the efficacy of emergency services in the detection of IPV cases, particularly during the current health crisis, and of the factors associated with detection by healthcare professionals, including opinions on sexist myths, requires further research [53,54]. Our hypothesis is that professionals showing favourable opinions on certain false beliefs or sexist myths perform a lower detection of IPV cases in emergency services.…”
Section: Introductionmentioning
confidence: 99%
“…The ED provides a unique opportunity for screening and early intervention for behaviours such as alcohol and substance use [10]. It is often the interface between the traditional health care system and vulnerable populations such as homeless persons [14], domestic violence victims [15] and older adults who are known to be at risk of violence-related events and substance abuse [16]. Various studies support the implementation of substance use screening tools for trauma patients in the ED [1,10] and our results suggest that patients with deliberate physical injuries could potentially deserve greater screening.…”
Section: Discussionmentioning
confidence: 99%